Meta-analysis of the effect of plyometric training on the athletic performance of youth basketball players - Zhou, Jing-Yi; Wang, Xin; Hao, Lei; Ran, Xiao-Wen; Wei, Wei (Frontiers in Physiology, 2024)
Objective: To investigate the effects of Plyometric Training (PT) on the athletic performance of youth basketball players (age 5 to 17.99) and to provide a theoretical basis for applying PT in basketball training practice. Method: PubMed, Web of Science, Cochrane Library, EBSCO and other data platforms were searched, and Meta-analysis was performed using STATA 16.0 software. Result: A total of 24 studies were included, with a sample size of 738 participants.The results showed that PT improved jumping, linear sprinting, change of direction (COD) speed, and balance in youth basketball players (P < 0.05) but did not significantly improve lower limb strength (P > 0.05). The results of subgroup analyses showed that:1) Regarding the effect of PT on different aspects of athletic performance, enhancements were found for vertical jump, 5-10m, 20-30m sprinting ability, velocity-oriented and force-oriented COD speed, and dynamic balance ability of youth basketball players. 2) When analyzing different participant subgroups, basketball players aged 5 to 10.99 and 11 to 14.99 years appeared to improve their jump, sprinting ability, and COD speed through PT training, whereas no improvements in sprinting ability and COD speed were found for players aged 15 to 17.99. Male and female youth basketball players could improve their jumping through PT, in contrast, straight-line sprinting ability and COD speed were significantly improved only by male youth basketball players, and balance ability was significantly improved only by female youth basketball players. 3)Regarding different training protocols, high-frequency PT (>2 times/week) with a low-volume (jumping ≤150 times/week) and Single-type PT (one specific movement) improved only jumping ability. In contrast, low-frequency PT (1-2 times/week) with a high-volume (jumping >150 times/week) and mixed-type PT (varied jumping drills) protocols significantly improved jumping, linear sprinting, COD speed, and balancing abilities. Conclusion: PT can enhance the jumping, linear sprinting, COD speed, and balance of youth basketball players, but it does not affect lower limb strength. It is recommended that coaches make full use of the trainingsensitive periods of young athletes by incorporating low-frequency, high-volume, and mixed-type PT into their regular training routines over the long term.